Emborrhoid – a new treatment method for hemorrhoids: case presentation - Zaks, Natalja; Mažrimas, Povilas; Poškus, Tomas; Misonis, Nerijus; Sokolovas, Vitalijus; Strupas, Kęstutis (Lietuvos chirurgija, 2017)
Background / Objective Hemorrhoids are a very common anorectal condition, affecting millions of people around the world and represent major medical and socioeconomic problem. New technique for treating symptomatic hemorrhoids has been introduced in to clinical practice. Only limited number of cases using this technique were reported. This was a first clinical case in Lithuania using this technique for treating hemorrhoids. 44 year-old-man underwent liver transplantation for B viral cirrhosis in 2011. He developed liver transplant cirrhosis, hepatorenal syndrome, portal hypertension, hiperuricaemia. He presented to us with recurrent episodes of massive rectal bleeding, requiring multiple transfusions, with hemoglobin as low as 45 g/l. Several episodes of conservative treatment for hemorrhoids was not effective. Because of thrombocytopenia, risk of intra- and postoperative bleeding usual choice of surgical or minimally invasive treatment for hemorrhoids was not possible. The choice of selective angiography and embolization was made. On the 30th of July 2015 the patient underwent visceral and selective mesenteric angiograms. Inferior mesenteric artery was canulated. Terminal branches of the inferior rectal artery were embolized using Interblock 18 microspirals. Three spirals were used. Rectal bleeding stopped. Proctoscopy was performed after three weeks. Hemorrhoidal cushions were reduced by approximately 70%. No recurrent bleeding was observed 23 months after the procedure. The patient safely underwent repeated liver transplantation within 1 month.Conclusions Embolization of inferior rectal arteries requires multidisciplinary approach. Emborrhoid is a safe, effective microinvasive treatment for hemorrhoids in patients, who are otherwise at high risk for surgical complications.
Keywords: hemorrhoidal disease; embolization; superior rectal artery; emborrhoid